Loss of SMAD4 staining in pre‐operative cell blocks is associated with distant metastases following pancreaticoduodenectomy with venous resection for pancreatic cancer. Issue 2 (24th March 2014) - Boone, Brian A.; Sabbaghian, Shirin; Zenati, Mazen; Marsh, J. Wallis; Moser, A. James; Zureikat, Amer H.; Singhi, Aatur D.; Zeh, Herbert J.; Krasinskas, Alyssa M.
<x xml:space="preserve">Abstract</x> Background and Objectives Venous resection of locally advanced pancreatic cancer is associated with increased morbidity and mortality; therefore identification of patients most likely to benefit from this aggressive surgical approach is an important goal. Loss of SMAD4 staining on resected specimens has been associated with outcomes. Few studies have evaluated the prognostic significance of SMAD4 staining of pre‐operative cell blocks, which would be useful in clinical decision making for patients with locally advanced disease. Methods Clinical data were retrospectively evaluated from all patients undergoing pancreaticoduodenectomy with venous resection. Immunohistochemical staining for SMAD4 was performed on pre‐operative cell blocks and subsequent post‐operative resections. Results One hundred seventeen patients underwent pancreaticoduodenectomy with venous resection. Sixty had sufficient specimens available for SMAD4 staining. SMAD4 loss was observed in 70% of resections and was associated with earlier time to metastatic disease. Pre‐operative SMAD4 loss correlated well with post‐operative staining and was associated with six times higher likelihood of developing metastases. Conclusion In this pilot study, preoperative SMAD4 staining showed a strong correlation with postoperative staining and predicted metastases in locally advanced cancer. Preoperative SMAD4 status may be considered as one of several factors when selecting patients most likely to benefit from aggressive en bloc venous resection. J. Surg. Oncol. 2014; 110:171–175. © 2014 Wiley Periodicals, Inc.